Fragment-based design of selective GPCR ligands guided by free energy simulations - Matricon, Pierre; Vo, Duc Duy; Gao, Zhan-Guo; Kihlberg, Jan; Jacobson, Kenneth A; Carlsson, Jens (Chemical communications (Cambridge, England), 2021)
Fragment-based drug discovery relies on successful optimization of weakly binding ligands for affinity and selectivity. Herein, we explored strategies for structure-based evolution of fragments binding to a G protein-coupled receptor. Molecular dynamics simulations combined with rigorous free energy calculations guided synthesis of nanomolar ligands with up to >1000-fold improvements of binding affinity and close to 40-fold subtype selectivity. Fragment-based drug discovery relies on successful optimization of weakly binding ligands for affinity and selectivity.